Detection of Brugia malayi in mosquitoes by the polymerase chain reaction - Vythilingam, Indra; Boaz, L.; Wa, Nzani (American Mosquito Control Association, 1998)
Accurate identification of filarial parasites in mosquitoes poses a major problem for the coordination of filariasis control programs. Traditional methods are tedious, and some are not specific enough to give satisfactory results. Amplification of specific gene sequences by primer-directed polymerase chain reaction (PCR) has been increasingly utilized as a diagnostic tool. However, current protocols for the extraction of parasite DNA from mosquito samples are tedious and could lead to failure of PCR amplification. We demonstrate that the use of Chelex is an efficient method for DNA extraction from mosquitoes and the parasite and that PCR amplification with primers specific for Brugia malayi yields a band of the expected size. The PCR products were transferred to a nylon membrane with Southern blotting, and a B. malayi-specific digoxigenin-labeled probe confirmed the sequence similarity of the PCR-amplified fragment and increased the sensitivity of the PCR assay. Use of this probe enabled us to detect PCR-amplified product from B. malayi even when a product was not visible on an ethidium bromide-stained agarose gel. This increased sensitivity allowed us to detect the parasite in the heads of mosquitoes.